Host biomarkers detected in saliva show promise as markers for the diagnosis of pulmonary tuberculosis disease and monitoring of the response to tuberculosis treatment. (May 2016) - Jacobs, Ruschca; Tshehla, Enock; Malherbe, Stephanus; Kriel, Magdalena; Loxton, Andre G.; Stanley, Kim; van der Spuy, Gian; Walzl, Gerhard; Chegou, Novel N.
Highlights: 33 biomarkers were evaluated in saliva samples from patients with presumed TB disease. A seven-marker saliva biosignature has potential in the diagnosis TB disease. Cytokines detected in saliva may be useful in monitoring of TB treatment response. Abstract: Background: There is an urgent need for new tools for the rapid diagnosis of tuberculosis (TB) disease in resource-constrained settings. Tests based on host immunological biomarkers maybe useful, especially if based on easily available samples. We investigated host biomarkers detected in saliva samples from individuals with suspected pulmonary TB disease, as tools for the diagnosis of TB disease and monitoring of the response to treatment. Methods: We collected saliva samples from 104 individuals that presented with symptoms requiring investigation for TB disease at a primary health care clinic in the outskirts of Cape Town, South Africa, prior to assessment for TB disease. We evaluated the concentrations of 33 host markers in stored saliva samples using a multiplex cytokine platform. Using a combination of clinical, radiological and laboratory results and a pre-established diagnostic algorithm, participants were later classified as having TB disease or other respiratory diseases (ORD). The diagnostic potentials of individual analytes were analysed by the receiver operator characteristics curve approach while the predictive abilities of combinations of analytes for TB disease were analysed by general discriminant analysis, with leave-one-out cross validation. Results: Of the 104 individuals enrolled, 32 were pulmonary TB cases. There were significant differences in the levels of 10 of the markers investigated between the patients with TB disease and those with ORDs. However, the optimal diagnostic biosignature was a seven-marker combination of salivary CRP, ferritin, serum amyloid P, MCP-1, alpha-2-macroglobulin, fibrinogen and tissue plasminogen activator. This biosignature diagnosed TB disease with a sensitivity of 78.1% (95% CI, 59.6–90.1%) and specificity of 83.3% (95% CI, 72.3–90.7%) after leave-one-out cross validation. When compared to baseline levels, the concentrations of 9 markers including granzyme A, MCP-1, IL-1β, IL-9, IL-10, IL-15, MIP-1β, ferritin and serum amyloid A changed significantly by months 2 or 6 after initiation of TB treatment, thereby indicating that they might be useful in monitoring the response to TB treatment. Conclusion: We have identified candidate biomarkers in saliva, which may be useful in the diagnosis of TB disease and monitoring of the response to TB treatment. These results require further validation in larger studies.